PLANNING CAPACITY FOR GENERAL AND THEMATIC BUREAUCRATIC REFORM IN MUSI BANYUASIN REGENCY - Ara Aydia Van Is; Siti Widharetno; Rikki Maulana Yusup (Universitas Negeri Makassar, 2026)
This study aims to analyse the planning capacity for General and Thematic Bureaucratic Reform in Musi Banyuasin Regency. The research uses a qualitative method with a descriptive approach and relies on primary data in the form of official documents, namely the final bureaucratic reform assessment report, the General and Thematic reform recap tables, and the 2025 action plan. The findings show that analytical capacity is reflected in the formulation of problems, indicators and targets for both reform tracks, although the linkage between internal governance indicators and thematic development outcomes is not yet articulated consistently. Operational capacity appears in detailed action plans in several areas, especially digital government and records management, while some General reform activities still do not have fully elaborated plans. Political capacity is indicated by the alignment of bureaucratic reform with regional development planning and the distribution of roles across local government organisations, yet a clear institutional focal point for integrating the General and Thematic tracks has not been firmly established. These results suggest that strengthening analytical linkages, balancing operational detail and clarifying integrative leadership would improve the overall planning capacity of bureaucratic reform in the regency.